Biodiesel production from crude rice bran oil and properties as fuel - Lin L. (2014)
This research reported on the successfully production of biodiesel by transesterification of crude rice bran oil (RBO). The process included three-steps. Firstly, the acid value of RBO was reduced to below 1 mg KOH/g by two-steps pretreatment process in the presence of sulfuric acid catalyst. Secondly, the product prepared from the first process was carried out esterification with an alkaline catalyst. The influence of four variables on conversion efficiency to methyl ester, i.e., methanol/RBO molar ratio, catalyst amount, reaction temperature and reaction time, was studied at this stage. The content of methyl ester was analyzed by chromatographic analysis. Through orthogonal analysis of parameters in a four-factor and three-level test, the optimum reaction conditions for the transesterification were obtained: methanol/RBO molar ratio 6:1, usage amount of KOH 0.9% w/w, reaction temperature 60 °C and reaction time 60 min. In the third step, methyl ester prepared from the second processing step was refined to become biodiesel. Fuel properties of RBO biodiesel were studied and compared according to ASTM D6751-02 and DIN V51606 standards for biodiesel. Most fuel properties complied with the limits prescribed in the aforementioned standards. The consequent engine test showed a similar power output compared with regular diesel but consumption rate was slightly higher. Emission tests showed a marked decrease in CO, HC and PM, however, with a slight increase in NOX. © 2008 Elsevier Ltd. All rights reserved.